Gambaran pasien mola hidatidosa di RSUP Prof. Dr. R.D. Kandou periode Januari 2020 sampai Desember 2022 - Estevania Kaligis; Wantania, John Johannes Ezwchiel; Wagey, Frank Mitchell Marvel (Jurnal Kedokteran Komunitas dan Tropik, 2024)
Background: Hydatidiform mole is a pathological pregnancy characterised by abnormal trophoblastic development, hindering foetal growth. This condition requires a better understanding of enhancing healthcare quality. Aim: To describe the profile of hydatidiform mole patients at Prof. Dr. R.D Kandou General Hospital, Manado, from January 2020 to December 2022. Methods: A quantitative descriptive study with a cross-sectional design was conducted, analysing data from 71 patients. Results: The most common age range was 20-35 years. In terms of parity, 42 patients were multiparous. Of the patients’ highest education level, 40 people had a senior high school level of education. There were 46 patients with haemoglobin levels of more than 11 g/dL. Vaginal bleeding was the most common symptom, which occurred in 48 patients. Conclusion: This study indicates hydatidiform mole predominantly affects women aged 20-35, multiparous, and with senior high school education, furthermore, vaginal bleeding is the most common symptom. These findings can improve awareness and healthcare quality for hydatidiform mole patients. Keywords: hydatidiform mole